Analisis Kinerja Keuangan PT Bank Rakyat Indonesia (Persero) Tbk Tahun 2023–2024 Berdasarkan Rasio Keuangan Perbankan Konvensional - Sheli Rachmawari; Widiar Onny Kurniawan; Seftya Khairun Nisa; Choirul Alam (Institut Nalanda, 2025)
This study aims to analyze the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk during the 2023–2024 period based on conventional banking financial ratios, including liquidity, profitability, and solvency aspects. The research employs a quantitative descriptive approach using financial ratio analysis consisting of the Loan to Deposit Ratio (LDR), Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR). The data were obtained from BRI’s officially published annual financial reports for 2023 and 2024. The findings reveal that BRI successfully maintained its financial stability amid national economic challenges, with total assets increasing by 1.42% and net profit rising by 9.3%. The LDR ratio of 83.5% indicates efficient credit distribution with sufficient liquidity, while the improved ROA and ROE of 3.3% and 21.2%, respectively, reflect management effectiveness in optimizing assets and equity. Moreover, a CAR of 22.4% confirms BRI’s strong capital adequacy in mitigating financial risks. Overall, this study concludes that BRI’s financial performance during 2023–2024 is highly sound and demonstrates strong adaptability to economic dynamics and digital transformation within the banking industry.